Quality Improvement and NCD Control: A Three-Year Primary Care Sustainability Assessment - Nongkynrih, Baridalyne; Kaur, Ravneet; Alwani, Anam Anil; Chandra, Ankit (National Journal of Community Medicine, 2026)
Objectives: This study aimed to evaluate the three-year sustainability of a quality improvement (QI) initiative designed to improve health records of individuals with hypertension and diabetes at a primary health facility in Delhi, India. Additionally, we used data from the records to calculate outcome indicators. Methods: This mixed methods study assessed sustainability using the National Health Service Sustainability Model and Guide. The World Health Organization’s cohort monitoring approach was used to calculate annual control rates, loss-to-follow-up rates and missed visits. Findings: The overall score for the sustainability assessment was 96.2%. Factors contributing to sustainability included the transition to digital health records, stakeholder engagement, process adaptation, improved clinical decision making, and strong senior leadership support. In all, 953 individuals living with hypertension and/or diabetes registered at the centre. Annual blood pressure and glycaemic control rates fluctuated from baseline to 2024. Records showed high loss-to-follow-up rates, and a large proportion of missed visits and missing data. Conclusion: The QI initiative of improved record keeping achieved a high sustainability score after three years. While digital records enabled calculating outcome indicators, these fell short of desired levels because of external factors, patients’ behaviour and poor availability of drugs and diagnostics.